Spectrally Resolved Exciton Polarizability for Understanding Charge Generation in Organic Bulk Hetero-Junction Diodes - Go, Enoch; Jin, Hyunjung; Yoon, Seongwon; Ahn, Hyungju; Kim, Joonsoo; Lim, Chanwoo; Kim, Ji-Hee; Din, Haleem Ud; Lee, Jung-Hoon; Jun, Yongseok; Yu, Hyeonggeun; Son, Hae Jung (American Chemical Society, 2024)
Despite decades of research, the dominant charge generation mechanism in organic bulk heterojunction (BHJ) devices is not completely understood. While the local dielectric environments of the photoexcited molecules are important for exciton dissociation, conventional characterizations cannot separately measure the polarizability of electron-donor and electron-acceptor, respectively, in their blends, making it difficult to decipher the spectrally different charge generation efficiencies in organic BHJ devices. Here, by spectrally resolved electroabsorption spectroscopy, we report extraction of the excited state polarizability for individual donors and acceptors in a series of organic blend films. Regardless of the donor and acceptor, we discovered that larger exciton polarizability is linked to larger pi-pi coherence length and faster charge transfer across the heterojunction, which fundamentally explains the origin of the higher charge generation efficiency near 100% in the BHJ photodiodes. We also show that the molecular packing of the donor and acceptor influence each other, resulting in a synergetic enhancement in the exciton polarizability.